Experimental investigation on the behaviour of thermal effluent in free surface flow - Ibrahim, Zulkiflee; Hashim, Noor Baharim; Abdul Latiff, Abd. Aziz; Halim, Herni; Mokhtar Kamal, Nurul Hana; Haron, Nuryazmeen Farhan (Faculty of Civil Engineering, 2008)
Thermal discharges such as from power station or industries polluting inland water bodies (rivers) causing degradation of water quality. The density of heated fluid is less than cold fluid and the positive buoyancy will force the heated fluid to disperse and spread at the ambient surface when it is discharged into the water bodies. Good understanding on thermal effluent behaviour in waterbodies leads good discharge management which can minimise the impact of thermal effluent pollution. An experimental study is conducted in the laboratory to investigate the mechanism of heat transport in free surface flow for ambient and thermal effluent flow rates. A multi-port diffuser pipe is placed at the channel bed in cross-flow direction to the ambient flow. Thermal effluent flow rates, Qe used in the experiment are 0.05 liter/s and 0.133 liter/s. Meanwhile, two ambient flow rates, Qa are fixed at 20 liter/s and 10 liter/s. The research focuses on thermal mixing process in near-field region. Among the parameters studied are effluent temperature, hydraulics characteristics of ambient flow (flow rate and velocity) and the characteristics of open channel including length, depth, and width. The dispersion profiles of thermal effluent are observed at various locations along the channel through the plotted isothermal lines. Meanwhile, the results of excess temperature (âˆ†T/Te) show that it decreases with the increasing of dispersion rate, KT as the thermal effluent moves downstream of the channel. The changes of ambient temperature, âˆ†T are studied through the plotted graphs. The results show that mixing process occurs in near-field and far-field regions. The temperature differences in near-field region are higher than far-field region because the area experienced high thermal effluent temperature, Te. Meanwhile, temperature differences in far-field region are low due to the effect of mixing between thermal effluent and ambient flow.